Composition and Characteristics of Construction Waste Generated by Residential Housing Project - Lau, H.H; Whyte, A.; Law, P.L. (International Journal of Environment Resource, 2008)
The construction industry is a major consumer of new materials. Given that material production for construction work accounts for a significant percentage of all energy consumed nationally in newly developing countries, it becomes vital that the construction industry strives to reduce waste at all stages of construction. However, the importance of these construction wastes in terms of types and sources have yet to be identified. Established systems to record quantitative data for the generation of construction waste have yet to be formally standardised and are still lacking across much of Europe and developing countries. Although categorisation of waste assists segregation of construction waste and increases the potential for reuse and recycling, little progress has been made in Sarawak, the largest state in Malaysia. To address this need, this pilot study is carried out as the logical first step towards construction waste management in Sarawak by categorisation of construction waste at residential construction projects. Through this study, useful information concerning waste assessment data necessary to achieve a better understanding of construction waste is obtained. Case studies involving quantification and classification of construction waste for several on-going residential construction projects in Miri City, Sarawak, Malaysia are presented. A database of information concerning the quantification of local construction waste was developed, in addition to current construction waste management practices.